Keep Calm, I Take Latin as a Subject. Issue 39 (2019) - Hanif, Huzefah
Abstract : 'Why would you choose Latin?' I have been asked an overwhelming amount of times, to which, over time, my simplified answer became 'because I didn't want to do drama'. I realised that my initial wearisome and somewhat preprepared speech wasn't able to effectively communicate my admiration for the intricate and sophisticated subject. Not only for how it enriches the mind in school but also how studying the history that comes with it leads to the understanding of the impact the classical times has had on our society, from the way it works to the way it doesn't. For these reasons, I firmly believe that all school pupils should have the opportunity to study Classics.